Implementation Of Green Practices At Ko Ko Mo Resort Gili Trawangan In Increasing Income - Ahmad, Ahmad; Anam, Ahmad Gautsul; Azim, Muhammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Green practices are very important for restaurants to do to reduce the impact of damage to the environment, but it is very unfortunate that Kokomo Resort has not fully implemented green practices for the benefit of environmental sustainability. There are also pros and cons regarding the importance of implementing green practices at Kokomo Resort which can be seen from the results of preliminary interviews conducted by the author. The location of this research was conducted at Kokomo Resort, located in Gili Indah Village, Gili Trawangan, Lombok. This research was conducted for 6 months, from January 2023 to June 2023. The object of this research is the implementation of green action and green food in increasing income at Kokomo Resort. The population in this study were Kokomo Resort managers and their staff, totaling 5 people. The sampling technique in this study used a total sampling technique, meaning that all members of the population are samples. The implementation of green practices at Kokomo Resort as a whole is quite good, with an average percentage of green action variables of 80%, green food of 82%, and green donation of 83%, all of which fall into the good category.